PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA SMK NEGERI 2 PONTIANAK TENTANG GETARAN - Islamiyati, Nur; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to find out the effect of discovery learning towards students’ learning result about vibration  in class XI SMK Negeri 2 Pontianak. It is a quasi experimental with the design of  non-equivalent control group design. There are 25 students of class XI TEI A as the control class and 26 students of class XI TOI as the experiment class and are determined with  purposive sampling. Based on scoring test, average score of the posttest from experiment class is obtained as 73,43, higher than control class with the average of 61,28. Based on the U-Mann Whitney test result, the sig value of 0,000>0,05, that means the Ha is accepted, meaning that there is a sig to the model of discovery learning. An effect size of 1,08 is obtained belonging to category high, its mean that the discovery learning model is effective towards scoring test about vibration in class XI SMK Negeri 2 Pontianak according to Coe.Keywords: Discovery Learning, Learning Outcomes